ATTAI VIDAL (LEECH THERAPY) IN SIDDHA SYSTEM OF MEDICINE AND THEIR CURRENT CONCEPT IN THERAPEUTIC APPLICATION - A REVIEW - Periyasami, *D.; Aarthy, K.; Monika, M.; Muthukumar, N.J. (International Journal of Ayurveda and Pharma Research, 2018)
The Siddha system of medicine is an unique traditional system of medicine practiced in Tamil speaking countries particularly India. In Siddha system of medicine the diseases were treated through internal and external medicine. In external medicine, the leech therapy is one which is used to treat various non-surgical and surgical cases. The leeches have been used for therapeutic purposes since their beginning of civilisation. Ancient Indian, Egyptian, Greek and Arab physicians were used the leeches for wide range of diseases such as inflammatory condition, skin diseases, respiratory disorders, eye diseases, cardiac diseases, urinary and reproductive diseases and dental diseases. The leeches are also used as one of the bloodletting methods in Unani, Ayurveda, and Modern science for various clinical conditions. Recently, researches on leech saliva revealed the presence nearly 100 biologically active compounds such as Hirudin, vasodilators, hyaluronidase, anaesthetics, fibrinases, antibacterial, collagenase etc. The above mentioned pharmacological compounds are injected into human body while sucking of the blood and are responsible for the anaesthetic, anti-inflammatory, anticoagulant and analgesic effect of leech application. In current scenario, the leech therapy is used for various diseases including life threatening diseases such as cardiovascular diseases, cancer, etc. in different system of medicine including modern medicine. Leech therapy is used in plastic and microsurgery as a protective tool against vascular congestion in modern medicine. The Scientific studies on leech saliva were proven and support the leech application in Siddha system of medicine.